(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: Carcinoma of the breast is one of the most common cancer in women and it is the second cause of cancer deaths only to lung cancer. Recent attention has been directed singularly at molecular classifications of breast cancer. Molecular subtypes have different prognostic and therapeutic implications. Objective: The aim of this study was to assess the ER, PR, and HER-2/neu reactivity pattern in breast carcinomas and to correlate this reactivity pattern with stage tumor size and lymph node metastasis. Methodology: This is a prospective analytical observational study was conducted in the North East Cancer Hospital and Department of Pathology of North East Medical College, Sylhet, Bangladesh during a 42 months period from July 2015 to December 2018. Result: Among 67 Cases of primary invasive breast carcinoma only one case was male and 66 were female. In aspect of tumor size most of the patient presented with 2 to 5cm tumor, 47(70.2%) cases and (80.6%) presented with more than 2cm tumor size. In our study 38(56.7%) cases of breast cancer found ER positive, 38.8%(26 cases) PR positive and 22.4% (15 cases) HER2/neu positive, most common presentation of the disease was at stage llB(29 cases,45%), lymph node positivity 46(68.7%) cases and lymph node negative 21(31.3%) cases, 5(7.5%)cases. In aspect of molecular subtyping we found luminl A 29 (43.3%) cases Luminal B 11.9% (8 cases) basal like 22(32.8%) cases and HER-2/neu over expressed 8(11.9%) cases. Conclusion: Cancer screening and early detection program can improve our scenario. Journal of Current and Advance Medical Research 2020;7(1): 30-35